The Association Between HLA Genetic Susceptibility Markers and Sonographic Enthesitis in Psoriatic Arthritis. Issue 5 (30th March 2018) - Polachek, Ari; Cook, Richard; Chandran, Vinod; Abji, Fatima; Gladman, Dafna; Eder, Lihi
Abstract : Objective: Enthesitis is an important pathophysiologic component of psoriatic arthritis (PsA). HLA genes are implicated in the pathogenesis of PsA. Little is known about the relationship between HLA genetic susceptibility markers and enthesitis in PsA patients. Our aim was to examine the association between HLA genetic susceptibility markers and sonographic enthesitis in PsA. Methods: A cross‐sectional analysis was conducted in patients with PsA. Sonographic enthesitis was assessed according to the Madrid Sonography Enthesitis Index scoring system. HLA genotyping was performed using sequence‐specific oligonucleotide probes. The association between 6 HLA susceptibility markers of PsA and the severity of sonographic enthesitis was assessed using multivariate regression models adjusted for age, sex, body mass index, and disease duration. Results: Two hundred twenty‐five patients were included, 57.8% of whom were men. The mean ± SD age was 56.1 ± 12.7 years, and the mean ± SD PsA duration was 16.9 ± 12.3 years. In the multivariate regression model, HLA–B*27 was associated with a higher enthesitis score (β = 4.24 [95% confidence interval 95% CI 0.02, 8.46]), and the interaction between HLA–B*27 and PsA duration was statistically significant, showing an increasing effect of HLA–B*27 with longer PsA duration (β = 4.62 [95% CI 1.38, 7.86]). Conclusion: HLA–B*27 is associated with more severe sonographic enthesitis in PsA, particularly in patients with longer disease duration. This finding highlights the possible role of genetic variants in predisposing to PsA subphenotypes.